Risk of Injury Due to Alcohol – Evaluating Potential Bias Using the Case-Crossover Usual-Frequency Method - Ye, Yu (2013)
BACKGROUND: The usual-frequency case-crossover method, comparing exposure before an event with typical exposure of the same person, is widely used to estimate the risk of injury related to acute alcohol use. Prior results suggest that risk estimates might be biased upward compared with other methods. METHODS: Using data from 15 emergency-room studies in 7 countries, we compared the usual-frequency case-crossover method with case-control analysis, using non-injury patients as controls. Control-crossover analysis was performed to examine potential bias and to adjust risk estimates. RESULTS: The cross-study pooled odds ratio (OR) of injury related to drinking was 4.7 (2.6–8.5) in case-crossover analysis and 2.1 (1.6–2.7) in case-control analysis. A control-crossover analysis found an indication of bias (OR=2.2 [1.8–2.8]), which was larger among less frequent drinkers. CONCLUSION: Findings suggest that the potential overestimation of injury risk based on the usual-frequency case-crossover method might be best explained by recall bias in usual-frequency estimates.